(untitled) (Universal International Scientific Journal, 2026)
The role and methodological foundations of STEAM (Science, Technology, Engineering, Arts, Mathematics) education in developing creativity and innovative thinking of students of pedagogical higher education are scientifically analyzed. According to the results of the study, students educated through the STEAM approach achieved higher results in creativity, critical thinking, teamwork, and application of practical knowledge compared to students who received traditional education. The article provides recommendations and promising proposals for the implementation of the STEAM approach in the education system of Uzbekistan.